Dramaturgy of Lesia Ukrainka and European Modern Drama: Text, Context - Stepan Khorob (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
It is difficult, if not impossible, to find in world literature an artistic phenomenon similar to the work of Lesya Ukrainka. For as long as a century scientists have been trying their best to highlight and explain this versatile astonishing national phenomenon: the phenomenon of the artist, human, woman. It is definitely not accidental that, avoiding analogies, Ivan Franko called Lesya Ukrainka nearly the only man "all across the whole of modern Ukraine" for her spirit strength and true Prometheus obsession, while Mykhailo Hrushevsky named her the "Ukrainian Shakespeare". According to Mykola Zerov, these similarities are clearly pronounced not in poetry (social lyrics, intimate lyrics), but primarily in her drama, which, in fact, makes up a unique modern world of ideas and images not only for national but also for the Western European literature.